2008
DOI: 10.1111/j.1365-2958.2008.06267.x
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of a Plasmodium falciparum cyclic nucleotide phosphodiesterase gene causes aberrant gametogenesis

Abstract: SummaryPhosphodiesterase (PDE) and guanylyl cyclase (GC) enzymes are key components of the cGMP signalling pathway and are encoded in the genome of Plasmodium falciparum. Here we investigate the role of specific GC and PDE isoforms in gamete formation -a process that is essential for malaria transmission and occurs in the Anopheles mosquito midgut following feeding on an infected individual. Details of the intracellular signalling events controlling development of the male and female gametes from their precurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
134
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(140 citation statements)
references
References 29 publications
5
134
1
Order By: Relevance
“…Parasites lacking GCβ were not impaired in gametogenesis, while in P . berghei revealed a severe defect in ookinete motility (Hirai et al ., 2006; Taylor et al ., 2008), indicating that GCα, not GCβ, is important for gametocyte activation.…”
Section: The Initiation Of Gametogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Parasites lacking GCβ were not impaired in gametogenesis, while in P . berghei revealed a severe defect in ookinete motility (Hirai et al ., 2006; Taylor et al ., 2008), indicating that GCα, not GCβ, is important for gametocyte activation.…”
Section: The Initiation Of Gametogenesismentioning
confidence: 99%
“…Interestingly, deletion of the gene coding for PDEδ leads to an impaired ability of P . falciparum to undergo gametogenesis, indicating that the tight regulation of intracellular cGMP concentrations is crucial for gametocyte activation and that premature, abnormally high cGMP levels have a deleterious effect on this process (Taylor et al ., 2008). …”
Section: The Initiation Of Gametogenesismentioning
confidence: 99%
“…As a consequence, it has been suggested that targeting P. falciparum PDEs should disrupt a range of physiological processes and weaken or kill the organism [15][16][17][18][19]. Interest in this area has been focussed on understanding the role of PDEs in the parasite life cycle [15,16,20]. In addition, Yuasa and co-workers have screened compounds against PfPDEa which has identified potential starting points for medicinal chemistry [21].…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, various studies have indicated that cyclic nucleotides are likely to play a major role in the cell biology of P. falciparum (including sexual development, hepatocyte infection, gametocytogenesis, cell cycle control, and exocytosis) [15,16]. As a consequence, it has been suggested that targeting P. falciparum PDEs should disrupt a range of physiological processes and weaken or kill the organism [15][16][17][18][19]. Interest in this area has been focussed on understanding the role of PDEs in the parasite life cycle [15,16,20].…”
Section: Introductionmentioning
confidence: 99%
“…cGMP signaling is essential for cardiovascular homeostasis; it controls relaxation and proliferation in vascular smooth muscle cells (Archer et al, 1994;Yu et al, 1997) in addition to contractility and hypertrophy in cardiac myocytes (Fiedler et al, 2002;Mohan et al, 1996). cGMP signaling is also essential for a variety of human pathogens including the malaria parasite Plasmodium falciparum (Taylor et al, 2008).…”
Section: Introductionmentioning
confidence: 99%